Determinansi Kinerja Guru: Sintesis Literatur Terhadap Variabel Kompensasi, Loyalitas, dan Faktor Psikologis Kerja - Sariman; Jauharul Manasik (Genius: Jurnal Ekonomi Dan Manajemen, 2025)
Teacher performance determination remains a central issue in improving the quality of national education, yet there is still a gap between enhanced compensation policies and actual teacher loyalty and performance in schools. This study aims to synthesize the literature on teacher performance determinants from the perspectives of compensation, loyalty, and work psychological factors through a systematic literature review with a thematic synthesis approach. Data were drawn from 35 scientific articles published in SINTA‑accredited national journals and reputable international journals from 2020 to 2026, accessed via Google Scholar, SINTA, DOAJ, Scopus, and Crossref, following the PRISMA protocol for article selection. Data analysis was conducted in three thematic synthesis stages: free coding, descriptive theme organization, and analytical theme development. The results highlight three main findings. First, compensation has a significant positive relationship with teacher loyalty, with an average correlation of , though the strength remains in the moderate range. Second, loyalty mediates the effect of compensation on teacher performance with an average effect of , but this mediation depends strongly on internal work motivation. Third, work psychological factors—especially self‑efficacy and work stress—show the strongest predictive effect on teacher performance, with an average correlation of , exceeding the direct influence of compensation. In conclusion, teacher performance is multidimensional and cannot be explained by economic variables alone; thus, policies to improve teacher welfare should be balanced with efforts to strengthen the psychosocial climate in schools.